Fischer Tropsch water composition study from distillation process in gas to liquid technology with ASPEN simulation - Nazeri, Abdul Rahman; Calvin, Jose Jol; Allene Albania, Linus; Dyg Sharifah Rozellia, Kamel Sharif; Verawaty, Ismail (Elsevier B.V., 2021)
Fischer-Tropsch is a polymerization reaction that produces a long chain of hydrocarbons such as linear paraffin, linear olefins, and water. Water is a by-product of Fischer Tropsch synthesis that contains impurities such as olefins and oxygen-containing compounds. Therefore, this study aims to analyze chemical oxygen demand (COD) level of Fischer Tropsch water from the distillation process by using Aspen simulation. Correspondingly, this study designs a Fischer Tropsch water distillation unit that can recover 1.2% of volatile organic compounds from the wastewater. In addition, this study has identified three (3) sections in the Fischer Tropsch water distillation unit which are distillation, recovery, and neutralization. Following this, a steady-state model is simulated through Aspen software with UNIQUAC-HOC as the thermodynamic model. The developed simulation model was found to be less than a 10% deviation as compared to the actual data from the natural gas processing plant located in Sarawak. Overall, the simulated distillation unit shows that 2100 tons of Fischer Tropsch water that can be treated at 120 C and 2.21 bar per day. The overhead product is an enriched volatile organic compounds stream while the bottom product is an enriched water stream. For this study, the processed water quality from distillation column has been compared with both stripped water quality in natural gas processing and National Water Standard Quality. Consequently, the comparison shows that the chemical oxygen demand of processed water level is at 600 ppm after distillation which follows the stripped water quality in natural gas processing, however, requires postwater treatment before being discharge to the surface water sources.